SNAPSHOT DALAM PROSA INDONESIA: KAJIAN STILISTIKA - Hasan Irsyad (Universitas Negeri Makassar, 2018)
Abstract: Snapshot in Indonesian Prose: Stylistics Study. This study aims to decribe snapshot’s form in Indonesian prose. This qualitative research uses Athirah by Alberthiene Endah and Semua Ikan di Langit by Ziggy Zezsyazeoviennazabrizkie as data sources. The result of the study show (1) snapshot is an ellipse sentence, (2) snapshot containing vanished repetition and repetition of meaning, (3) snapshot’s form is divided into three: (a) first form, basic sentence followed by snapshot sentence; (b) second form, snapshot sentence followed by basic sentence; and (c) modified form, snapshot sentences enriched by other clause.